Traction : how any startup can achieve explosive customer growth - Weinberg, Gabriel; Mares, Justin (New York, New York : Portfolio/Penguin, 2015)
"Most startups don't fail because they can't build a product. Most startups fail because they can't get traction, "--Amazon.com.
Preface: Traction Trumps Everything -- Traction Channels -- Traction Thinking -- Bullseye -- Traction Testing -- Critical Path -- Targeting Blogs -- Publicity -- Unconventional PR -- Search Engine Marketing (SEM) -- Social and Display Ads -- Offline Ads -- Search Engine Optimization (SEO) -- Content Marketing -- Email Marketing -- Viral Marketing -- Engineering as Marketing -- Business Development (BD) -- Sales -- Affiliate Programs -- Existing Platforms -- Trade Shows -- Offline Events -- Speaking Engagements -- Community Building -- Acknowledgments -- Appendix: Midds Ring Tests -- Index.
Includes index.
Keywords: New business enterprises; Marketing -- Management; Success in business